A clay stabilizer for oil well fracturing and preparation method thereof

By synthesizing zwitterionic monomers containing cyclodextrin groups and initiating polymerization with methoxy polyethylene glycol acrylate, clay stabilizers with rigid structures were prepared, and clay stabilizers with high temperature and mineralization in the prior art were solved. The problem of insufficient temperature and salt resistance under conditions has achieved high anti-swelling and scrubbing resistance, which is suitable for oil well fracturing projects.

CN118978649BActive Publication Date: 2024-12-31LIAONING LIAOHE JINYU ENERGY GROUP CO LTD SCIENTIFIC RESEARCH BRANCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475484.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-31
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing clay stabilizers have poor resistance to temperature and salt under high temperature and high mineralization conditions, and their protection effect on the formation is limited, making it difficult to stabilize clay particles for a long time, affecting the fracturing effect of oil wells.

Method used

By synthesizing zwitterionic monomers containing cyclodextrin groups and initiating polymerization with methoxy polyethylene glycol acrylate, acrylic acid, etc., a clay stabilizer with a rigid structure is prepared to enhance its multi-point adsorption, temperature and salt resistance.

Benefits of technology

The clay stabilization effect of high anti-swelling, scrub resistance and high temperature and high salt resistance is achieved, and the recovery rate of oil well fracturing and reservoir protection ability are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention relates to the technical field of oil production, and discloses a clay stabilizer for oil well fracturing and a preparation method thereof. 1,3-diaminopropane, 1,3-propane sultone and allyl cyclodextrin are used as raw materials, and a cyclodextrin-based zwitterionic monomer is obtained through a chemical grafting reaction, and then polymerization is initiated with acrylic acid and methoxy polyethylene glycol acrylate to obtain the clay stabilizer for oil well fracturing. The clay stabilizer contains quaternary ammonium salt cations, which can be inserted between clay crystal layers to neutralize the negative charge on the clay surface. The sodium sulfonate hydration group can be adsorbed on the surface of clay particles to form a dense hydration layer, thereby preventing and delaying the contact between water molecules and the clay surface. The introduction of cyclodextrin side chains increases the steric hindrance and has a strong ability to resist salt hydrolysis. The clay stabilizer prepared by the invention has good anti-swelling performance, good washing resistance, temperature resistance and salt resistance, and is suitable for oil well fracturing and production engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petroleum exploitation, in particular to a clay stabilizer for oil well fracturing and a preparation method thereof. Background Art

[0002] With the continuous development of oil fields, people pay more and more attention to the protection technology of reservoirs. In the process of water injection, acidification and fracturing in oil fields, clay minerals contained in oil reservoirs, such as kaolinite, montmorillonite, illite and chlorite, will hydrate, swell and disperse when encountering external water or water-based substances, which will lead to blockage of pores and channels, reduce formation permeability, damage reservoirs, and thus affect the final recovery rate. The role of clay stabilizers in protecting oil layers is to prevent the hydration, expansion and dispersion of clay minerals in the reservoir and block the seepage channels. Therefore, the use of clay stabilizers is indispensable.

[0003] At present, the commonly used clay stabilizers are mainly small molecule quaternary ammonium salts or polyquaternary ammonium salts surfactants and polymers formed by their combination with inorganic salts. Although they have certain anti-swelling properties, their temperature resistance, salt resistance and erosion resistance are limited, and they cause great damage to the formation. Inorganic salt clay stabilizers are widely available, low in price, simple to use and maintain, but can only temporarily stabilize clay particles, are not resistant to erosion, and this type of clay stabilizer cannot produce multi-point adsorption. Anionic polymers have low flocculation ability and are prone to precipitation when encountering high-priced inorganic cations such as magnesium and calcium, and the anti-swelling effect is not very ideal. Cationic polymers have the advantages of strong adsorption capacity, little influence by pH value, and strong adaptability to formations, but their temperature resistance and erosion resistance are limited.

[0004] Zwitterionic polymers carry both positive and negative charges, and have shown great advantages in terms of inhibition, maintaining stable drilling fluid performance and reducing filter loss performance. Patent No. CN114805682B discloses an amphoteric clay stabilizer and a preparation method thereof, wherein the main amphoteric clay stabilizer is obtained by polymerizing the prepared dimethyl dodecyl allyl ammonium chloride with sodium styrene sulfonate and diallylamine, and then compounding with potassium chloride, ammonium sulfate, dodecyl trimethyl ammonium chloride and water to obtain the amphoteric clay stabilizer, which has the advantage of a high anti-swelling rate. However, under high temperature and high mineralization conditions, the zwitterionic polymer lacks a rigid structure in the molecule, and the molecular chain curls in large quantities, resulting in poor temperature and salt resistance, and a significant decrease in inhibition ability. In order to further improve the temperature and salt resistance of zwitterionic polymers; the present invention aims to synthesize a zwitterionic monomer containing a cyclodextrin group, and initiate polymerization with methoxy polyethylene glycol acrylate, acrylic acid, etc. to obtain a clay stabilizer containing zwitterions and a rigid structure, which has the characteristics of multi-point adsorption, good temperature and salt resistance, and high anti-swelling rate, and is suitable for industrial oil well fracturing and mining projects. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a clay stabilizer for oil well fracturing and a preparation method thereof, which can prevent clay minerals from hydrating, swelling, dispersing and migrating, reduce the damage to the permeability of low permeability oil layers, and have good temperature and salt resistance.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a clay stabilizer for oil well fracturing is carried out according to the following steps:

[0008] Step (1), under a nitrogen atmosphere, add cyclodextrin-based sodium sulfonate tertiary amine monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add 3-bromopropylene, stir to react, and after the reaction is completed, cool to room temperature, and concentrate under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer.

[0009] Step (2), under a nitrogen atmosphere, acrylic acid, cyclodextrin-based zwitterionic monomer, methoxy polyethylene glycol acrylate and deionized water are added to a reaction flask, and after stirring evenly, ammonium persulfate is added dropwise at a rate of 0.8-1.2 mL / min. After the addition is completed, the mixture is reacted at 75-90° C. for 1-3 h, cooled to 40-50° C., and triethylamine is added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0010] Furthermore, in step (1), the molar ratio of the sodium cyclodextrin sulfonate tertiary amine monomer to 3-bromopropylene is 1:2.5-4.

[0011] Furthermore, in step (1), the reaction temperature is 90-110° C. and the reaction time is 24-48 h.

[0012] Furthermore, in step (2), the molar ratio of acrylic acid, cyclodextrin-based zwitterionic monomer, methoxy polyethylene glycol acrylate, and ammonium persulfate is 1:0.03-0.15:0.25-0.4:0.005-0.012.

[0013] Furthermore, the preparation method of the sodium cyclodextrin sulfonate tertiary amine monomer in step (1) is carried out according to the following steps:

[0014] Step S1, under a nitrogen atmosphere, add 1,3-diaminopropane and tetrahydrofuran to a reaction flask, stir evenly, add 1,3-propane sultone and sodium hydride, stir to react, after the reaction is completed, extract with ethyl acetate and deionized water, concentrate the organic phase, recrystallize with ethanol, filter, and obtain a sodium bisaminosulfonate monomer.

[0015] Step S2, under a nitrogen atmosphere, add sodium bisamine sulfonate monomer and methanol to a reaction flask, stir evenly, add allyl cyclodextrin, stir to react, after the reaction is completed, cool to room temperature, concentrate under reduced pressure, wash with deionized water, and obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0016] Furthermore, in step S1, the molar ratio of 1,3-diaminopropane, 1,3-propane sultone and sodium hydride is 1:2.05-2.2:2.3-2.8.

[0017] Furthermore, in step S1, the reaction temperature is 55-70° C., and the reaction time is 8-16 h.

[0018] Furthermore, in step S2, the molar ratio of sodium bisaminosulfonate monomer to allyl cyclodextrin is 1:2.02-2.1.

[0019] Furthermore, in step S2, the reaction temperature is 40-55° C., and the reaction time is 12-24 h.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The invention uses 1,3-diaminopropane, 1,3-propane sultone, allyl cyclodextrin and 3-bromopropylene as raw materials, obtains cyclodextrin-based zwitterionic monomers through chemical grafting reaction, and then initiates polymerization with acrylic acid and methoxy polyethylene glycol acrylate to obtain a clay stabilizer for oil well fracturing. The clay stabilizer contains quaternary ammonium salt cations, which can be inserted between clay crystal layers to neutralize the negative charge on the clay surface, and can produce a stronger chemical adsorption effect on the surface of clay particles than non-ionic polar adsorption groups, and is easy to associate to form a network structure in a chain bundle, and achieves a complete coating effect on clay particles through adsorption, so that the repulsive force between clay particles is weakened; the sodium sulfonate hydration group in the structure can be adsorbed on the surface of clay particles to form a dense hydration layer, which prevents and delays the contact between water molecules and the clay surface, and plays a role in preventing hydration expansion.

[0022] The introduction of cyclodextrin side groups in the molecular chain of the clay stabilizer provides a large number of hydroxyl groups with strong polarity, which can be adsorbed on the clay surface through hydrogen bonding, preventing water molecules from continuing to enter the area between the clay crystal layers, bridging the clay crystal layers, and inhibiting clay expansion; at the same time, the presence of the hydrophobic cavity of cyclodextrin provides a natural barrier to prevent water molecules from entering the clay crystal layers, enhancing the ability to inhibit clay hydration expansion; the clay stabilizer belongs to a polymer macromolecular structure, and the long-chain molecules in its structure can be adsorbed to multiple crystal layers and clay particles at the same time, thereby effectively reducing the hydration expansion and osmotic hydration expansion of the clay surface, inhibiting the dispersion of clay and the migration of particles, so it is difficult for low-valent cations in the clay to be replaced from the surface of clay particles through ion exchange or washed off by other acid flows, oil flows, and water flows; the clay stabilizer contains a relatively large cyclodextrin side chain, which increases the steric hindrance and has a strong ability to resist salt hydrolysis, so as to achieve the effect of long-term stabilization of the clay.

[0023] The clay stabilizer of the present invention has a wide range of raw material sources, simple synthesis and preparation processes, does not produce any by-products, and is safe and environmentally friendly. The clay stabilizer of the present invention has the advantage of a high anti-swelling rate. Under the condition of a use concentration of 0.2wt%, the anti-swelling rate reaches more than 99%. The clay stabilizer prepared by the present invention has good anti-swelling performance, and at the same time has washability, temperature resistance and salt resistance, and can be used for the development of oil and gas fields. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise specified, the raw materials and reagents used in this application are commercially available or can be prepared by known methods.

[0026] The preparation of allyl cyclodextrin was carried out with reference to "Synthesis and Structural Characterization of 6-O-allyl-β-cyclodextrin" in "China Adhesives", Vol. 19, No. 12, December 2010: 1.135 g of β-cyclodextrin was dissolved in 60 mL of equal volumes of anhydrous N,N-dimethylformamide and anhydrous dimethyl sulfoxide, 3.54 g of sodium hydroxide was added while stirring, stirred at room temperature for 1 hour, naturally cooled to 5-10°C, 8 mL of allyl bromide was added twice while stirring, and the reaction was continued for 48 hours. After the reaction was completed, it was allowed to stand for 2 hours, concentrated under reduced pressure, and the residue was washed with acetone several times, filtered and dried to obtain allyl cyclodextrin.

[0027] Polyethylene glycol methyl ether acrylate, CAS number is 32171-39-4, structural formula is , molecular weight is 1000.

[0028] 1,3-Diaminopropane, CAS number is 109-76-2.

[0029] 1,3-Propane sultone, CAS number is 1120-71-4.

[0030] 3-Brompropylene, CAS number is 106-95-6.

[0031] Embodiment 1:

[0032] (1) Under nitrogen atmosphere, 85 mmol of 1,3-diaminopropane and 340 mL of tetrahydrofuran were added to a reaction flask. After stirring, 180.2 mmol of 1,3-propane sultone and 205 mmol of sodium hydride were added. The mixture was reacted at 65 °C for 12 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated, recrystallized with ethanol, and filtered to obtain sodium bis(amino)sulfonate monomer.

[0033] (2) Under nitrogen atmosphere, add 75 mmol of sodium bisamine sulfonate monomer and 750 mL of methanol into a reaction flask, stir evenly, then add 154.5 mmol of allyl cyclodextrin, react at 45 °C for 16 h, cool to room temperature, concentrate under reduced pressure, and wash with deionized water to obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0034] (3) Under nitrogen atmosphere, add 60 mmol of cyclodextrin-based sodium sulfonate tertiary amine monomer and 1080 mL of N,N-dimethylformamide to the reaction flask, stir evenly, add 210 mmol of 3-bromopropylene, react at 100°C for 32 hours, cool to room temperature, and concentrate under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer. The preparation reaction process is as follows:

[0035] (4) Under a nitrogen atmosphere, 100 mmol of acrylic acid, 3 mmol of cyclodextrin-based zwitterionic monomer, 35 mmol of methoxy polyethylene glycol acrylate and 75 mL of deionized water were added to a reaction flask. After stirring evenly, 0.8 mmol of ammonium persulfate was added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was reacted at 80 °C for 2 h, cooled to 45 °C, and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0036] Embodiment 2:

[0037] (1) Under nitrogen atmosphere, 150 mmol of 1,3-diaminopropane and 300 mL of tetrahydrofuran were added to a reaction flask. After stirring, 307.5 mmol of 1,3-propane sultone and 345 mmol of sodium hydride were added. The mixture was reacted at 70°C for 8 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated, recrystallized with ethanol, and filtered to obtain sodium bis(amino)sulfonate monomer.

[0038] (2) Under nitrogen atmosphere, 120 mmol of sodium bisamine sulfonate monomer and 960 mL of methanol were added to a reaction flask. After stirring evenly, 242.4 mmol of allyl cyclodextrin was added. The mixture was reacted at 55 °C for 12 h. The mixture was cooled to room temperature, concentrated under reduced pressure, and washed with deionized water to obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0039] (3) Under nitrogen atmosphere, add 96 mmol of cyclodextrin-based sodium sulfonate tertiary amine monomer and 1440 mL of N,N-dimethylformamide into the reaction flask. After stirring evenly, add 240 mmol of 3-bromopropylene. React at 110 °C for 24 h, cool to room temperature, and concentrate under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer.

[0040] (4) Under a nitrogen atmosphere, 100 mmol of acrylic acid, 6 mmol of cyclodextrin-based zwitterionic monomer, 25 mmol of methoxy polyethylene glycol acrylate and 60 mL of deionized water were added to a reaction flask. After stirring evenly, 0.5 mmol of ammonium persulfate was added dropwise at a rate of 0.8 mL / min. After the addition was completed, the mixture was reacted at 90 °C for 1 h, cooled to 50 °C, and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0041] Embodiment 3:

[0042] (1) Under nitrogen atmosphere, 32 mmol of 1,3-diaminopropane and 160 mL of tetrahydrofuran were added to a reaction flask. After stirring, 70.4 mmol of 1,3-propane sultone and 89.6 mmol of sodium hydride were added. The mixture was reacted at 55 °C for 16 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated, recrystallized with ethanol, and filtered to obtain sodium bis(amino)sulfonate monomer.

[0043] (2) Under nitrogen atmosphere, add 25 mmol of sodium bisamine sulfonate monomer and 300 mL of methanol into a reaction flask. After stirring evenly, add 52.5 mmol of allyl cyclodextrin. React at 40 °C for 24 h. Cool to room temperature, concentrate under reduced pressure, and wash with deionized water to obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0044] (3) Under nitrogen atmosphere, 18 mmol of cyclodextrin-based sodium sulfonate tertiary amine monomer and 360 mL of N,N-dimethylformamide were added to the reaction flask. After stirring evenly, 72 mmol of 3-bromopropylene was added. The mixture was reacted at 90 °C for 48 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer.

[0045] (4) Under a nitrogen atmosphere, 100 mmol of acrylic acid, 9 mmol of cyclodextrin-based zwitterionic monomer, 40 mmol of methoxy polyethylene glycol acrylate and 80 mL of deionized water were added to a reaction flask. After stirring evenly, 1.2 mmol of ammonium persulfate was added dropwise at a rate of 1.2 mL / min. After the addition was completed, the mixture was reacted at 75 °C for 3 h, cooled to 40 °C, and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0046] Embodiment 4:

[0047] (1) Under nitrogen atmosphere, 70 mmol of 1,3-diaminopropane and 245 mL of tetrahydrofuran were added to a reaction flask. After stirring, 147 mmol of 1,3-propane sultone and 175 mmol of sodium hydride were added. The mixture was reacted at 65 °C for 15 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated, recrystallized with ethanol, and filtered to obtain sodium bis(amino)sulfonate monomer.

[0048] (2) Under a nitrogen atmosphere, 65 mmol of sodium bisamine sulfonate monomer and 685 mL of methanol were added to a reaction flask. After stirring evenly, 135 mmol of allyl cyclodextrin was added. The mixture was reacted at 45 °C for 18 h. The mixture was cooled to room temperature, concentrated under reduced pressure, and washed with deionized water to obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0049] (3) Under nitrogen atmosphere, 50 mmol of cyclodextrin-based sodium sulfonate tertiary amine monomer and 900 mL of N,N-dimethylformamide were added to the reaction flask. After stirring evenly, 175 mmol of 3-bromopropylene was added. The mixture was reacted at 105 °C for 32 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer.

[0050] (4) Under a nitrogen atmosphere, 100 mmol of acrylic acid, 12 mmol of cyclodextrin-based zwitterionic monomer, 30 mmol of methoxy polyethylene glycol acrylate and 75 mL of deionized water were added to a reaction flask. After stirring evenly, 0.8 mmol of ammonium persulfate was added dropwise at a rate of 0.9 mL / min. After the addition was completed, the mixture was reacted at 85 °C for 3 h, cooled to 50 °C, and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0051] Embodiment 5:

[0052] (1) Under nitrogen atmosphere, 48 mmol of 1,3-diaminopropane and 168 mL of tetrahydrofuran were added to a reaction flask. After stirring, 103.2 mmol of 1,3-propane sultone and 120 mmol of sodium hydride were added. The mixture was reacted at 65 °C for 10 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated, recrystallized with ethanol, and filtered to obtain sodium bis(amino)sulfonate monomer.

[0053] (2) Under nitrogen atmosphere, 35 mmol of sodium bisamine sulfonate monomer and 310 mL of methanol were added to a reaction flask. After stirring evenly, 72.8 mmol of allyl cyclodextrin was added. The mixture was reacted at 50 °C for 24 h. The mixture was cooled to room temperature, concentrated under reduced pressure, and washed with deionized water to obtain sodium cyclodextrin sulfonate tertiary amine monomer.

[0054] (3) Under nitrogen atmosphere, 30 mmol of cyclodextrin-based sodium sulfonate tertiary amine monomer and 550 mL of N,N-dimethylformamide were added to the reaction flask. After stirring evenly, 108 mmol of 3-bromopropylene was added. The mixture was reacted at 110 °C for 48 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer.

[0055] (4) Under a nitrogen atmosphere, 100 mmol of acrylic acid, 15 mmol of cyclodextrin-based zwitterionic monomer, 35 mmol of methoxy polyethylene glycol acrylate and 75 mL of deionized water were added to a reaction flask. After stirring evenly, 1 mmol of ammonium persulfate was added dropwise at a rate of 1.1 mL / min. After the addition was completed, the mixture was reacted at 90 °C for 3 h, cooled to 45 °C, and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0056] Comparative Example 1

[0057] Under a nitrogen atmosphere, 100 mmol acrylic acid, 3 mmol allyl cyclodextrin, 35 mmol methoxy polyethylene glycol acrylate and 75 mL deionized water were added to a reaction flask. After stirring evenly, 0.8 mmol ammonium persulfate was added dropwise at a rate of 1 mL / min. After the addition was completed, the mixture was reacted at 80° C. for 2 h, cooled to 45° C., and triethylamine was added to adjust the pH to neutral to obtain a clay stabilizer for oil well fracturing.

[0058] Comparative Example 2

[0059] Under nitrogen atmosphere, 100 mmol acrylic acid and 3 mmol dimethyldiallylammonium chloride (structural formula: , CAS No. 7398-69-8), 3mmol of sodium 4-vinylbenzenesulfonate (structural formula , CAS number is 2695-37-6), 35mmol methoxy polyethylene glycol acrylate and 75mL deionized water, after stirring evenly, 0.8mmol ammonium persulfate is added dropwise at a rate of 1mL / min. After the addition is completed, react at 80℃ for 2h, cool to 45℃, add triethylamine to adjust the pH to neutral, and obtain a clay stabilizer for oil well fracturing.

[0060] Static clay anti-swelling performance test: refer to the centrifugation method in SY / T5971-2016 "Performance Evaluation Method of Clay Stabilizer for Oil and Gas Field Fracturing Acidification and Water Injection" to test the anti-swelling rate of the clay stabilizer. Weigh 0.2g of the clay stabilizer prepared in the embodiment and the comparative example, add 100mL of distilled water and shake well to obtain a clay stabilizer solution; weigh 0.50g of sodium bentonite, put it into a 10mL centrifuge tube, add 10mL of clay stabilizer solution, shake well, place it at room temperature for 2h, put it into a centrifuge, centrifuge it at a speed of 1500r / min for 15min, read the volume V1 of sodium bentonite after expansion, replace the clay stabilizer solution with 10mL of distilled water and kerosene respectively, and measure the expansion volume V2 and V1 of bentonite in water and kerosene; Anti-swelling rate calculation formula: B=(V2-V1) / (V2-V0)×100%. Wherein: B: anti-swelling rate (%); V0: expansion volume of bentonite in kerosene (mL); V1: expansion volume of bentonite in clay stabilizer (mL); V2: expansion volume of bentonite in distilled water (mL).

[0061] Table 1 Static anti-expansion performance test

[0062]

[0063] It can be seen from the test results in the above table that with the increase of the content of cyclodextrin-based zwitterionic monomers, the static anti-swelling rate of the clay stabilizer gradually increases, and Example 5 reaches 99.6%. This is because on the one hand, the clay stabilizer contains quaternary ammonium salt cations inserted between the clay crystal layers, neutralizing the negative charge on the clay surface, and can produce a stronger chemical adsorption effect on the surface of the clay particles than the non-ionic polar adsorption group, and is prone to association to form a network structure in the chain bundle, and the complete coating effect on the clay particles is achieved through adsorption, so that the repulsive force between the clay particles is weakened; the sodium sulfonate in its structure The hydration group can be adsorbed on the surface of clay particles to form a dense hydration layer, preventing and delaying the contact between water molecules and the clay surface, and preventing hydration expansion; on the other hand, the introduction of cyclodextrin side groups in the clay stabilizer provides a large number of hydroxyl groups with strong polarity, which can be adsorbed on the clay surface through hydrogen bonding, preventing water molecules from continuing to enter the area between clay crystal layers, bridging the clay crystal layers, and inhibiting clay expansion; at the same time, the presence of the hydrophobic cavity of cyclodextrin provides a natural barrier to prevent water molecules from entering the clay crystal layer, and enhances the ability to inhibit clay hydration expansion. Comparative Example 1 does not contain zwitterions, and Comparative Example 2 does not contain cyclodextrin, and their expansion rates are both lower than those of the embodiments.

[0064] Water washing resistance test: The water washing resistance of the clay stabilizer is determined by referring to the method specified in SY / T 5971-2016 "Performance Evaluation Method of Clay Stabilizer for Fracturing, Acidification and Water Injection in Oil and Gas Fields". Weigh 0.2g of the clay stabilizer prepared in the examples and comparative examples, add 100mL of distilled water and shake well to obtain a clay stabilizer solution, mix with 0.50g of bentonite and centrifuge, record the expansion volume V1, remove the supernatant, add 10mL of distilled water, shake well and let stand for 2h, load into a centrifuge, centrifuge at 1500r / min for 15min, record the expansion volume V2, repeat the above steps 3-8 times, read the volume of bentonite after expansion each time, and judge the water washing resistance of the clay stabilizer according to the change of the anti-swelling rate.

[0065] Table 2 Washability test

[0066]

[0067] It can be seen from the test results in the above table that the clay stabilizer solution prepared by the present invention has a good initial anti-swelling rate, and the anti-swelling rate after 8 water washings is above 85%, which is maintained at a relatively high level. This is because the clay stabilizer belongs to a polymer macromolecular structure, and the long-chain molecules in its structure can be adsorbed to multiple crystal layers and clay particles at the same time, thereby effectively reducing the hydration expansion and osmotic hydration expansion of the clay surface, inhibiting the dispersion of the clay and the migration of the particles, so it is difficult for the low-valent cations in the clay to be replaced from the surface of the clay particles through ion exchange or washed away by other acid flows, oil flows, and water flows; therefore, the clay stabilizer prepared by the present invention has both economic and anti-scouring effects, and can achieve the effect of long-term stabilization of the clay.

[0068] Temperature resistance test: Weigh 0.2 g of the clay stabilizer prepared in the examples and comparative examples, add 100 mL of distilled water and shake well to obtain a clay stabilizer solution, put it into a high-pressure container, heat it to 150 ° C at a heating rate of 1 ° C / min and place it for 30 days, refer to SY / T 5971-2016 "Performance Evaluation Method of Clay Stabilizer for Fracturing Acidification and Water Injection in Oil and Gas Fields", and use the clay stabilizer after high temperature treatment to perform expansion experiment.

[0069] Salt resistance test: Prepare standard brine with a certain mineralization degree according to the mass ratio (NaCl:CaCl2:MgCl2·6H2O=7:0.6:0.4), add 2% clay stabilizer solution by mass, and use the centrifugal method to refer to SY / T 5971-2016 "Performance Evaluation Method of Clay Stabilizer for Fracturing Acidification and Water Injection in Oil and Gas Fields" to conduct a swelling experiment with the clay stabilizer treated with brine.

[0070] Table 3 Temperature and salt resistance test

[0071]

[0072] It can be seen from the test results in the above table that the anti-swelling rate of the clay stabilizer after being treated with high temperature and salt water is above 80%. This is because the clay stabilizer contains a relatively large cyclodextrin side chain agent, which increases the steric hindrance and has a strong resistance to salt hydrolysis. This shows that the clay stabilizer prepared by the present invention has good anti-swelling performance, and is resistant to washing and high temperature, and can be used for the development of oil and gas fields.

[0073] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application; the methods used in the present application are conventional methods unless otherwise specified.

Claims

1. A method for preparing a clay stabilizer for oil well fracturing, characterized in that: The preparation method is carried out according to the following steps: Step (1), under a nitrogen atmosphere, add cyclodextrin-based sodium sulfonate tertiary amine monomer and N,N-dimethylformamide to a reaction flask, stir evenly, add 3-bromopropylene, stir to react, and after the reaction is completed, cool to room temperature, and concentrate under reduced pressure to obtain a cyclodextrin-based zwitterionic monomer; Step (2), under a nitrogen atmosphere, add acrylic acid, cyclodextrin-based zwitterionic monomer, methoxy polyethylene glycol acrylate and deionized water into a reaction flask, stir evenly, and then drop ammonium persulfate at a rate of 0.8-1.2 mL / min. After the dropwise addition is completed, react at 75-90° C. for 1-3 h, cool to 40-50° C., add triethylamine to adjust the pH to neutral, and obtain a clay stabilizer for oil well fracturing; The preparation method of the sodium cyclodextrin sulfonate tertiary amine monomer in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add 1,3-diaminopropane and tetrahydrofuran to a reaction flask, stir evenly, then add 1,3-propane sultone and sodium hydride, stir to react, after the reaction is completed, extract with ethyl acetate and deionized water, concentrate the organic phase, recrystallize with ethanol, filter, and obtain a sodium bisaminosulfonate monomer; Step S2, under a nitrogen atmosphere, add sodium bisamine sulfonate monomer and methanol to a reaction flask, stir evenly, add allyl cyclodextrin, stir to react, after the reaction is completed, cool to room temperature, concentrate under reduced pressure, wash with deionized water, and obtain sodium cyclodextrin sulfonate tertiary amine monomer.

2. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In the step (1), the molar ratio of the sodium cyclodextrin sulfonate tertiary amine monomer to 3-bromopropylene is 1:2.5-4.

3. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In the step (1), the reaction temperature is 90-110° C. and the reaction time is 24-48 hours.

4. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In the step (2), the molar ratio of acrylic acid, cyclodextrin-based zwitterionic monomer, methoxy polyethylene glycol acrylate, and ammonium persulfate is 1:0.03-0.15:0.25-0.4:0.005-0.

012.

5. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In step S1, the molar ratio of 1,3-diaminopropane, 1,3-propane sultone and sodium hydride is 1:2.05-2.2:2.3-2.

8.

6. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In step S1, the reaction temperature is 55-70° C. and the reaction time is 8-16 h.

7. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In the step S2, the molar ratio of the sodium bisaminosulfonate monomer to the allyl cyclodextrin is 1:2.02-2.

1.

8. The method for preparing a clay stabilizer for oil well fracturing according to claim 1, characterized in that: In step S2, the reaction temperature is 40-55° C. and the reaction time is 12-24 h.

9. A clay stabilizer for oil well fracturing, characterized in that: Obtained by the preparation method according to any one of claims 1 to 8.